Do Central and Eastern Europe Countries Play a Role in the Belt and Road Initiative? The Case of Chinese OFDI into the CEE–16 Countries - Bieliński, Tomasz; Markiewicz, Magdalena; Oziewicz, Ewa (Comparative Economic Research. Central and Eastern Europe, 2019)
The main aim of the article was to analyze the motives behind the FDI decisions of Chinese companies’ capital engagement in Central and Eastern Europe. The article examines the applicability of existing theoretical concepts towards Chinese outward foreign direct investment (OFDI). Chinese OFDI patterns have been found to be consistent with Dunning’s investment development path (IDP) theory, but research shows that OFDI to CEE countries is additionally driven by specific motives different than in other regions. The study has proved that one of the major purposes is to get access to the EU common market. Additionally, data analysis has revealed that CEE countries that are not part of the EU attract proportionally more Chinese FDI than those that have easier access to EU funds.